PENGARUH CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP AGRESIVITAS PAJAK PERUSAHAAN - Delitha Magfira E.G; Murtanto Murtanto (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
The objective of this research is to examine and analyze the effect of corporate governance, firm size and profitability towards tax aggressiveness. The sampel was extracted using purposive sampling method, which is 61 mining companies that listed in Indonesia Stock Exchange for the period of 2017-2019. This research uses multiple linear regression analysis method. The result from this research showed that independent commissioners and firm size have negative impact towards tax aggresiveness, while institusional ownership have a positif impact towards tax aggressiveness, and audit committee and profitability have no impact towards Tax Aggressiveness.